Antimicrobial Resistance and Extended-Spectrum Beta-Lactamase Genes in Enterobacterales, Pseudomonas and Acinetobacter Isolates from the Uterus of Healthy Mares - Thomson, Pamela; García, Patricia; Río, Camila del; Castro, Ricardo I.; Núñez, Andrea; Miranda, Carolina (MDPI, 2023)
Antibiotic-resistant bacteria are a growing concern for human and animal health. The objective of this study was to determine the antimicrobial resistance and extended-spectrum beta-lactamase genes in Enterobacterales, Pseudomonas spp. and Acinetobacter spp. isolates from the uterus of healthy mares. For this purpose, 21 mares were swabbed for samples, which were later seeded on blood agar and MacConkey agar. The isolates were identified using MALDI-TOF and the antimicrobial susceptibility test was performed using the Kirby–Bauer technique. To characterize the resistance genes, a polymerase chain reaction (PCR) scheme was performed. Of the isolates identified as Gram-negative, 68.8% were Enterobacterales, represented by E. coli, Enterobacter cloacae, Citrobacter spp., and Klebsiella pneumoniae; 28.1% belonged to the genus Acinetobacter spp.; and 3.1% to Pseudomonas aeruginosa. A 9.3% of the isolates were multidrug-resistant (MDR), presenting resistance to antibiotics from three different classes, while 18.8% presented resistance to two or more classes of different antibiotics. The diversity of three genes that code for ESBL (blaTEM, blaCTX-M and blaSHV) was detected in 12.5% of the strains. The most frequent was blaSHV, while blaTEM and blaCTX-M were present in Citrobacter spp. and Klebsiella pneumoniae. These results are an alarm call for veterinarians and their environment and suggest taking measures to prevent the spread of these microorganisms.
Keywords: Antibiotic resistance; ESBL; Útero; Yeguas